Fiscal Policy Instruments in Islamic Macroeconomics Perspectives - Santoso, Ari Fajar; Janwari, Yadi; Hasanuddin, Muhammad; Tamba, Dheddy Abdi; Abdurahman, Lukman (Strata International Journal of Social Issues, 2025)
This study explores the role of fiscal policy instruments within the framework of Islamic macroeconomics, mainly through the principles of Maqasid al-Shariah, which emphasize social justice and societal well-being. Using a qualitative research approach with a descriptive analysis method, this study incorporates literature review and triangulation techniques, like document analysis and expert interviews, to assess the effectiveness of zakat, waqf, and sukuk in supporting economic stability and social welfare. The findings indicate that these instruments significantly contribute to poverty reduction and infrastructure development, yet challenges remain in governance, transparency, and public awareness. Strategic measures such as regulatory strengthening, institutional capacity building, and financial literacy campaigns are necessary to enhance the impact of Islamic fiscal policies. Additionally, leveraging technological innovations—such as digital zakat platforms and innovative waqf management models—can improve efficiency and transparency. By addressing these challenges, Islamic fiscal policy has the potential to serve as a sustainable and ethical alternative to conventional fiscal systems.